Socioeconomic factors and shifts in ideological orientation among political parties: Parliamentary elections in Slovakia from 1998 to 2020 - Tomáš Bačo; Eduard Baumöhl (ZBW - Leibniz Information Centre for Economics, 2021)
We analyze the election results of political parties and ideological blocs in parliamentary elections held in the Slovak Republic from 1998 to 2020 across 79 districts (LAU 1 level). Interestingly, correlations among parties' election results between consecutive elections are very high across all elections from 1998 until 2016, meaning that any increase or decrease in electoral support was almost uniform across all districts from one election to another. The last elections disrupted this trend, and in line with the significantly lower degree of correlation with prior elections for all ideological groups, we observe territorially heterogeneous voting behavior. Especially in districts with left-wing support, the electorate shifted toward what we refer to as ideologically vague parties. Within a seemingly unrelated regression (SUR) framework, we show that systematic influence of economic variables on the election results is present only for right-wing parties. For other ideological blocs, age and population density appear to be more influential factors. The “economically rational” right-wing election camp, however, has exhibited a decline in electoral support.
Keywords: D72; E24; E61; P20; 330; Economic voting; Elections; Popularity; Government support; Populism